Do procrastinators get worse sleep? Cross-sectional study of US adolescents and young adults - Xiaoyu Li; Orfeu M. Buxton; Yongjoo Kim; Sebastien Haneuse; Ichiro Kawachi (Elsevier, 2020)
Procrastination is a widespread habit that has been understudied in the realm of health behaviors, especially sleep. This study aimed to examine the cross-sectional relationships between procrastination and multiple dimensions of sleep in a large national sample of US adolescents and young adults. A random sample of 8742 students from 11 US universities provided self-reports of procrastination (measured by the General Procrastination Scale-Short Form with scores ranging from 1 to 5) and sleep behaviors including social jetlag (the absolute difference between mid-sleep times on weeknights and weekend nights), sleep duration (mean weekly, weeknight, and weekend night), insomnia symptoms (trouble falling/staying asleep), daytime sleepiness, and sleep medication use. Multiple linear regression and Poisson regression models adjusted for socio-demographic and academic characteristics as well as response propensity weights. Higher levels of procrastination were significantly associated with greater social jetlag (β = 3.34 min per unit increase in the procrastination score; 95% CI [1.86, 4.81]), shorter mean weekly sleep duration (β = −4.44 min; 95% CI [-6.36, −2.52]), and shorter weeknight sleep duration (β = −6.10 min; 95% CI [-8.37, −3.84]), but not weekend night sleep duration. Moreover, procrastination was associated with insomnia symptoms (Relative Risk (RR) = 1.27; 95% CI [1.19, 1.37]) and daytime sleepiness (RR = 1.32; 95% CI [1.27, 1.38]), but not sleep medication use. The results were robust to adjustment for anxiety and depressive symptoms. Procrastination was associated with greater social jetlag, shorter sleep duration, and worse sleep quality. If causal, the results suggest that interventions to prevent and manage procrastination might help students to improve their sleep health.